Hydrodynamics of offshore structures with specific focus on wind energy applications. (April 2015) - Benitz, M.A.; Lackner, M.A.; Schmidt, D.P.
Abstract: This review covers the broad scope of ocean hydrodynamics on offshore marine structures, laying the framework for studying offshore wind energy with a variety of engineering methods. First, water wave theory is described beginning with the fundamental equations of fluid mechanics. A variety of wave theories are discussed, beginning with linearized wave theory, and continuing with Stokes, cnoidal and solitary wave theory. The regions of wave applicability for different theories are shown, summarizing the discussion of water wave theory. Following the introduction of water wave theory, ocean physics is introduced. This section includes ocean wave generation, random waves, spectral representation and commonly used wave spectra, including the Pierson–Moskowitz and JONSWAP spectra. Next, wave–body interaction is presented, first looking at static and then dynamic loads. The dynamic load discussion covers waves, added mass and impulse loads. The section on wave–body interaction concludes with a review of recent literature on wave–body interactions, with emphasis on offshore wind energy. Additionally, a sample of existing engineering tools for modeling hydrodynamics on offshore wind turbines is presented. Finally, finite volume methods are presented to lay the groundwork for reviewing recent computational fluid dynamics research relating to the wave–body interaction problem. The review culminates in a review of recent CFD research.